Barriers and Drivers for Innovation in Times of Crisis - Cândido, Ana Clara; Wielevick, Patrícia Feronha; Zimmermann, Ricardo Augusto (Revista de Negócios, 2016)
The economic crisis which started in 2008 has demonstrated more clearly the importance of conjuncture aspects for organizational results evidencing associated opportunities and vulnerabilities. In such a context, if on one hand innovation is affected by investment reduction by most enterprises, on the other it has shown to be one of the â€œantidotesâ€ against the crisis and appears as fertile soil for investments, in the organizational as well as in the territorial context. Enterprises and countries which maintained or even raised efforts toward innovation have demonstrated a higher resilience in times of difficulty. This study aims at identifying opportunities and threats to the innovation performance of firms by means of the study of the crisis effects upon external facilitators and barriers. Besides the literature review, case studies developed in Portuguese and Brazilian enterprises are used for the analysis of the practical effects of the identified aspects in two distinct realities in what concerns the economic crisis. The results show that although Portugal has suffered the crisis effects, in a general way, more than Brazil, when we look to innovation performance, Portugal has shown better results than Brazil during and after the crisis. This study contributes to enterprise and academic purposes since it classifies factors which influence innovation positive or negatively in times of crisis.